2019
DOI: 10.1080/24750573.2019.1610144
|View full text |Cite
|
Sign up to set email alerts
|

Normative data and factorial structure of the Turkish version of the temperament and character inventory-revised (Turkish TCI-R)

Abstract: OBJECTIVE: In this study, we aimed to examine the validity, reliability, and factor structure of the TCI-R in a Turkish sample. METHODS: Participants were 1026 (786 female, 240 male) college students at Hasan Kalyoncu University in Turkey. The study protocol was approved by the local Ethics Committee. Sociodemographic information of the participants was collected and the TCI-R, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Personality Belief Questionnaire (PBQ) were administered. All stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Persistence is associated with positive personality traits of hardworking, determined, perfectionist and enthusiastic temperament. 4,5 People with this temperament tend to continue the behavior despite frustration and fatigue. In this regard, the result of our study seems to be compatible with the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Persistence is associated with positive personality traits of hardworking, determined, perfectionist and enthusiastic temperament. 4,5 People with this temperament tend to continue the behavior despite frustration and fatigue. In this regard, the result of our study seems to be compatible with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The Temperament and Character Inventory (TCI) was developed by Cloninger et al 4 It is a dimensional model for the conceptualization and classification of personality that includes both normal personality traits and personality disorders. 4,5 It evaluates four temperament and three character traits: Novelty seeking (NS), harm avoidance (HA), reward dependence (RD), and persistence (P) are temperament components. Self-directedness (SD), cooperation (C), and self-transcendence (ST) are character components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCI‐R has been used in many countries and in many languages, and its psychometric features have been found to be valid and reliable in the assessment of personality. The validity, reliability, and factorial structure of the Turkish version have been studied by Kose et al [49], who reported Cronbach alpha coefficients above 0.7 for all dimensions. The copyright of the Turkish TCI‐R is held by Kose and permission to use the inventory in the research was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Among character traits, Self-Directedness (S) was divided into five subscales (S1: Responsibility, S2: Purposefulness, S3: Resourcefulness, S4: Self-acceptance, and S5: Enlightened 2nd nature); Cooperativeness (C) into five subscales (C1: Socialacceptance, C2: Empathy, C3: Helpfulness, C4: Compassion, and C5: Integratedconscience); and Self-Transcendence (ST)was divided into three subscales (ST1: Self-forgetfulness, ST2:Transpersonalidentification, and ST3: Spiritualacceptance). TCI was developed by Cloninger, and the Turkish version of TCI was developed by Kose et al5,17,18…”
mentioning
confidence: 99%